Conservative treatment strategies for endometrioid ovarian cysts: A review - Tatyana A. Makarenko; Darya E. Galkina; Elena A. Borisova (IP Berlin A.V., 2023)
Endometriosis remains one of the most topical diseases in current gynecology and is a multifactorial condition with an overgrowth of tissue morphologically and functionally similar to the endometrium outside the uterine cavity. One of the most frequently diagnosed forms of endometriosis is endometrioid ovarian cysts. An important feature of the clinical course of ovarian endometriosis is its negative impact on reproductive function and the recurrent nature of the disease, which may require repeated surgeries with even greater damage to the ovarian tissue. Therefore, the development of a long-term drug treatment strategy for patients with a history of endometrioid cysts aimed at preventing recurrences is urgently needed. According to domestic and foreign clinical guidelines, progestagen hormone therapy is recommended as first-line therapy for such patients. One of the most clinically studied drugs with a favorable efficacy and safety profile proven in numerous studies is dienogest. The paper presents the experience of foreign and domestic authors in conservative therapy in patients with a history of endometrioid cysts using dienogest in terms of recurrence prophylaxis.